2016
DOI: 10.1111/wrr.12432
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts related to hypertrophic scarring in burn injuries

Abstract: Scarring following burn injury and its accompanying aesthetic and functional sequelae still pose major challenges. Hypertrophic scarring (HTS) can greatly impact patients’ quality of life related to appearance, pain, pruritus and even loss of function of the injured body region. The identification of molecular events occurring in the evolution of the burn scar has increased our knowledge; however, this information has not yet translated into effective treatment modalities. Although many of the pathophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 91 publications
0
58
0
Order By: Relevance
“…Fibroproliferative disorders of the skin, such as hypertrophic scarring (HTS), are characterized by dysregulated collagen production and result in raised, thick, and inflexible scars [1][2][3]. HTS occurs most commonly after burn injury, surgery, or excessive inflammation and can dramatically diminish patient quality of life [1,[3][4][5]. HTS contractures and rigidity can limit range of motion and impair day-to-day activities.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroproliferative disorders of the skin, such as hypertrophic scarring (HTS), are characterized by dysregulated collagen production and result in raised, thick, and inflexible scars [1][2][3]. HTS occurs most commonly after burn injury, surgery, or excessive inflammation and can dramatically diminish patient quality of life [1,[3][4][5]. HTS contractures and rigidity can limit range of motion and impair day-to-day activities.…”
Section: Introductionmentioning
confidence: 99%
“…This migration facilitates wound closure rat, re-epithelialization and angiogenesis [92]. Adipose-derived (ADSCs) and mesenchymal stem cells(MSCs)have been commonly investigated for scar treatment [93].…”
Section: Stem Cellsmentioning
confidence: 99%
“…Hypertrophic scar (HS) reflects the dysfunctional response from the skin during injury especially burns and surgery, which leads to excessive deposition of fibroblast and collagen and thick elevated scar/fibrosis [1]. Post-burn HS presents an emotional and physical burden on the patient owing to excessive pain, pruritus, discomfort, disability (joint contracture) and disfigurements [2]. Epidemiological studies have indicated that about 40 -70 % of thermal injury (burn wound) result in HS.…”
Section: Introductionmentioning
confidence: 99%